High Contrast PET Imaging of GRPR Expression in Prostate Cancer Using Cobalt-Labeled Bombesin Antagonist RM26. (10th August 2017) - Mitran, Bogdan; Thisgaard, Helge; Rosenström, Ulrika; Dam, Johan Hygum; Larhed, Mats; Tolmachev, Vladimir; Orlova, Anna
Abstract : High gastrin releasing peptide receptor (GRPR) expression is associated with numerous cancers including prostate and breast cancer. The aim of the current study was to develop a 55 Co-labeled PET agent based on GRPR antagonist RM26 for visualization of GRPR-expressing tumors. Labeling with 57 Co and 55 Co, stability, binding specificity, and in vitro and in vivo characteristics of 57 Co-NOTA-PEG2 -RM26 were studied. NOTA-PEG2 -RM26 was successfully radiolabeled with 57 Co and 55 Co with high yields and demonstrated high stability. The radiopeptide showed retained binding specificity to GRPR in vitro and in vivo. 57 Co-NOTA-PEG2 -RM26 biodistribution in mice was characterized by rapid clearance of radioactivity from blood and normal non-GRPR-expressing organs and low hepatic uptake. The clearance was predominantly renal with a low degree of radioactivity reabsorption. Tumor-to-blood ratios were approximately 200 (3 h pi) and 1000 (24 h pi). The favorable biodistribution of cobalt-labeled NOTA-PEG2 -RM26 translated into high contrast preclinical PET/CT (using 55 Co) and SPECT/CT (using 57 Co) images of PC-3 xenografts. The initial biological results suggest that 55 Co-NOTA-PEG2 -RM26 is a promising tracer for PET visualization of GRPR-expressing tumors.